The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bjophthalmol-2015-307110
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in visual field testing

Abstract: HVF testing induces more anxiety than HRT. Increased pretest anxiety may reduce HVF test reliability. Increased test experience or interventions aimed at reducing pretest anxiety may result in improved test reliability and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Overall, however, participants clearly prefer the VR device (see Attractiveness dimension -Figure 6). This is in line with studies that have shown that SAP has been quite unpopular among patient groups (Gardiner and Demirel, 2008;Chew et al, 2016;McTrusty et al, 2017). These findings are significant as it gives credibility to the FOVE as an effective and enjoyable screening tool.…”
Section: Virtual Reality Is Preferred Across All Aspects Of the User Experience Questionnairesupporting
confidence: 89%
“…Overall, however, participants clearly prefer the VR device (see Attractiveness dimension -Figure 6). This is in line with studies that have shown that SAP has been quite unpopular among patient groups (Gardiner and Demirel, 2008;Chew et al, 2016;McTrusty et al, 2017). These findings are significant as it gives credibility to the FOVE as an effective and enjoyable screening tool.…”
Section: Virtual Reality Is Preferred Across All Aspects Of the User Experience Questionnairesupporting
confidence: 89%
“… 2 In addition, patients undergoing SAP have been found to experience higher levels of anxiety than those undergoing other tests, such as retinal imaging, and those who were anxious before undergoing SAP produced poorer reliability test results. 3 There is a need for a more acceptable visual field test for patients.…”
Section: Introductionmentioning
confidence: 99%
“…A number of our patients spontaneously reported feeling less anxious when tested with the novel method. Since anxiety compromises visual field testing reliability, 7 it is possible that our novel technique may improve patient test performance in part due to reduced psychological stress.Most of the patients had visual field defects that encompassed the entire 24-2 zone. We believe that further development of our method should employ testing strategies that cover a much wider zone.…”
Section: Discussionmentioning
confidence: 99%